Freshwater prawn framing a manul for the culture of Macrobrachium rosenbergii - New, Michael B. (FAO, 1982)
This manual has been prepared on the basis of Thai experience in the farming of the giant freasrwater prawn Macrobrachium rosenbergii. It has a practical orientation, as it was written for extension and fishery officers as well as for practising,.......